Chocolate spread emulsion: Effects of varying oil types on physico-chemical properties, sensory qualities and storage stability - Wan Anwar Fahmi, Wan Mohamad; Che Abdullah, Abu Bakar; Arif, Said (2019)
Chocolate spread emulsion is an alternative product to the conventional dry-based chocolate spreads. The main objective of this study was to evaluate the use of three potential oils; palm olein, olive oil and corn oil, in the production of chocolate spread emulsions. The palm olein chocolate spread was the easiest to spread compared to the olive oil and corn oil chocolate spread emulsions. The melting point of the commercial spread was higher than the emulsion samples, but the sensory scores of the samples were comparable to the commercial spread. The proximate analyses of the samples with different oil types gave no significant difference in the values of moisture, ash, protein, fat, fibre and carbohydrate. Further study on the storage stability of all samples for 28 days at 28 and 10 °C revealed that the firmness of the spread emulsions generally decreased by week, while the water activity (aw) values decreased during the storage at 28 °C and increased at 10 °C. There was no oil separation and microbial growth observed on the chocolate spread samples throughout the storage period at both temperatures.